MORTALITY RATES AND YIELD PER RECRUIT OF CATFISH TACHYSURUS TENUISPINIS (DAY) - Dan, S S (Indian Journal of Fisheries, 2011)
The mortality rates and yield per recruit of the catfish, Tachysurus tenuispinisare estimated from mean sizes and age composition. The total instantaneousmortality rate ramges between OJ80 and 1.10. The natural mortality (M) was 0.5.1.The yield per recruit. YW/iR was maximum when F = 0.3. As the fishing mortality(F) already generated is considerable, caution is indicated against steppingup the fishing effort aay further to increase the catch of th& species.